Recent Patents in Cell Therapy for Amyotrophic Lateral Sclerosis - D. Haim, Eithan; N. Williams, Stephanie; R. Sanberg, Paul; Garbuzova-Davis, Svitlana N. (Recent Patents on Regenerative Medicine, 2015)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive motor neuron degeneration in the brain and spinal cord. Reliable treatment options for this disease are limited due to complexity and multifactorial causes of motor neuron damage. Cell therapy might be a promising treatment for ALS. Numerous preclinical studies have validated the feasibility of cell therapy using various cell types and routes of administration. These cell therapy approaches largely take one of two distinct therapeutic strategies: neuroprotection or motor neuron replacement. Despite some promising results, the success of cell therapy in ALS might rely on a combinative strategy that exploits the benefits of both neuronal cell protection and replacement. Although, ongoing clinical trials provide promising results in cell therapy for treatment of ALS patients, some challenges still facing potential cell therapy development. In this review, current cell products and patent technology related to cell therapeutic strategies are discussed. A detailed discussion of this topic might offer vital insight into the future and viability of cell therapy for ALS.
Keywords: patents